Factorise:

Question:

Factorise:
ab(x2 + y2) − xy(a2 + b2)

Solution:

We have:

$a b\left(x^{2}+y^{2}\right)-x y\left(a^{2}+b^{2}\right)=a b x^{2}+a b y^{2}-a^{2} x y-b^{2} x y$

$=a b x^{2}-a^{2} x y+a b y^{2}-b^{2} x y$

$=a x(b x-a y)+b y(a y-b x)$

$=a x(b x-a y)-b y(b x-a y)$

$=(b x-a y)(a x-b y)$

$\therefore a b\left(x^{2}+y^{2}\right)-x y\left(a^{2}+b^{2}\right)=(b x-a y)(a x-b y)$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now